Antioxidant status and metabolic profile of buffalo during different growth stages - BHULLAR, PREETINDER; NAYYAR, SHASHI; SANGHA, S P S (The Indian Journal of Animal Sciences, 2011)
The metabolic profile and the erythrocytic levels of lipid peroxidation, glutathione peroxidase and superoxide dismutase activities were determined along with the plasma levels of vitamin E, ß-carotene and vitamin E in different growth stages of female buffalo, viz. calves (neonatal, transitional and ruminant), heifers (prepubertal and pubertal), pregnant (early, mid and late), postpartum lactating and dry buffaloes. The lipid peroxidation level decreased with age and increased during pregnancy. The superoxide dismutase activity was higher during late pregnancy than early pregnancy. The levels of ß-carotene, vitamin E, vitamin C, cholesterol and HDL-cholesterol were higher in heifers than the calves. During pregnancy, ß-carotene and vitamin E levels decreased whereas lipid peroxidation increased.